2001
DOI: 10.1111/j.1475-6811.2001.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the events that elicit jealousy among homosexuals

Abstract: When individuals are asked which event would upset them more-a partner's emotional infidelity or a partner's sexual infidelity-among heterosexuals more men than women select a partner's sexual infidelity as the most distressing event, whereas more women than men select a partner's emotional infidelity as the most upsetting event. Because homosexuals' mating psychology is unlike that of heterosexuals, the present study examined which of these two events is more upsetting in a sample of 237 Dutch homosexuals. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 31 publications
4
39
2
2
Order By: Relevance
“…Therefore, it seems this sexual orientation difference has emerged as a function of the incredibly high levels of distress to emotional infidelity reported by heterosexual women, lesbian women, and gay men (Harris, 2002;Sheets & Wolfe, 2001). Heterosexual men have also been found to be significantly more distressed by sexual infidelity than lesbian women (Harris, 2002), which contradicts other findings that show heterosexual men and lesbians respond similarly to the infidelity dilemmas (deSouza et al, 2006;Dijkstra et al, 2001). …”
Section: List Of Tablescontrasting
confidence: 54%
See 4 more Smart Citations
“…Therefore, it seems this sexual orientation difference has emerged as a function of the incredibly high levels of distress to emotional infidelity reported by heterosexual women, lesbian women, and gay men (Harris, 2002;Sheets & Wolfe, 2001). Heterosexual men have also been found to be significantly more distressed by sexual infidelity than lesbian women (Harris, 2002), which contradicts other findings that show heterosexual men and lesbians respond similarly to the infidelity dilemmas (deSouza et al, 2006;Dijkstra et al, 2001). …”
Section: List Of Tablescontrasting
confidence: 54%
“…Another emergent pattern is that lesbians, gay men, and heterosexual women tend to report similar levels of distress to emotional infidelity (Bailey et al, 1994;Harris, 2002;Sheets & Wolfe, 2001). Lesbian women have also been found to be more upset by sexual than emotional infidelity when compared to gay men (Dijkstra et al, 2001), but in most cases, no differences were found between these two groups (Bailey et al, 1994;deSouza et al, 2006;Dijkstra et al, 2001;Sheets & Wolfe, 2001). It is possible that lesbians hold similar views as heterosexual men (sexual infidelity as more upsetting) relative to gay men, whereas gay men hold similar views as heterosexual women (emotional infidelity as more upsetting) relative to lesbian women.…”
Section: List Of Tablesmentioning
confidence: 89%
See 3 more Smart Citations